Prediction of Spontaneous Stone Expulsion by Serum C-Reactive Protein in Patients with Distal Ureteric Calculi - Raya, Akash; Rai, Binod K; Yadav, Aditya P; Shahi, Sanjiv K (Journal of Institute of Medicine Nepal, 2023)
Introduction: Ureter obstruction caused by a ureteral stone triggers inflammatory change in the proximal submucosal layer and prevents passage of the stone which can increase C-reactive protein level. The present study was designed to see if CRP plays a role in predicting the expulsion of distal ureteric calculi of <10 mm in patients presenting to urology department. Methods: A cross-sectional study was done at National Medical College, Department of Surgery, Birgunj from January 2022 to June 2022. Total of 60 cases were included in the study who presented with distal ureteric calculi. Level of CRP was recorded and divided into <6 mg/dl and >6 mg/dl. Size of stone and rate of spontaneous expulsion was noted. Results: Among the 60 cases, 34 (56.7%) were males and 26 (43.3%) were females. Mean age of the study cases was 36.1±11.76 years and mean size of stone 6.72±1.54 mm. among the total cases 28 (47%) had CRP level <6mg/dl and 32 (53%) had CRP level >6mg/dl. Among the total cases 35 (58.3%) did not pass stone spontaneously and the size of stone was 6.9743±1.74598 mm. spontaneous passage of stone was not seen in 21 (60%) male and 14 (40%) female cases. Significant difference (p=<0.001) was seen between expulsion and non-expulsion of stone. Conclusion: Measurement of CRP at the time of presentation with distal ureteric calculi of small size can help the urologist to predict whether spontaneous expulsion is possible or not.